Caracterização e avaliação da estabilidade do ácido lactobiônico e de diferentes lactobionatos produzidos por Zymomonas mobilis visando à utilização na área farmacêutica - Delagustin, Maria Gabriele (My University, 2017)
Lactobionic acid and its salts (lactobionate) are substances that have several applications in pharmaceutical area. These products were obtained by enzymatic complex glucose-fructose-oxidoreductase (GFOR)/gluconolactonase (GL) present in the periplasm of Zymomonas mobilis cells that were immobilized in calcium alginate. In the reactions catalyzed by this enzyme system, the medium pH must be controlled at slightly acid values. For this purpose, NaOH, KOH, or Ca(OH)2 were used and as a result the respective salts were formed. The kinetic study on the formation of sodium, potassium and calcium lactobionate and lactobionic acid itself was followed by the steps of purification, characterization and evaluation of the physicochemical stability, aiming the potential use of these compounds in the pharmaceutical area. In the assays for the bioproduction of sodium, potassium or calcium lactobionates, yields of 74, 77 and 84% were obtained, respectively. In repeated bioconversion batches, totalizing 96 hours of use of the biocatalyst, yields of 80 and 56% were attained for calcium and potassium lactobionate. In the salts purification step, purity levels of approximately 95% were achieved, and subsequently these compounds were characterized by high performance liquid chromatography, mass spectrometry, and C13 NMR. In the studies of accelerated, long term and forced degradation stability, the production of sodium, potassium and calcium lactobionate was carried out at higher reaction volume. The products were purified and then evaluated together with lactobionic acid that was obtained by ion-exchange from sodium lactobionate, and with a commercial lactobionic acid (Sigma-Aldrich). In the accelerated and long term stability tests, it was demonstrated the stability of all compounds when exposed to 30 and 40oC and of 75%of relative humidity for up to six months. On the other hand, the presence of lactobionolactone was identified in samples of compounds in the acid form. With respect to the forced degradation tests, sodium, potassium and calcium lactobionates and lactobionic acid have shown to be stable after exposing to both acidic and alkaline solutions and the temperatures evaluated. However, degradation was observed in the treatment with oxidative solution, with a zero-order degradation kinetics for the salts forms and second-order for lactobionic acid. High concentrations of products - sodium, potassium and calcium lactobionate - were achieved by using the Ca-alginate immobilized GFOR/GL complex. Considering the set of information obtained in regarding to physicochemical characterization, it was demonstrated the high stability of these compounds in front of different parameters evaluated, endorsing the legal minimum requirements for their application in the pharmaceutical area.
O ácido lactobiônico e seus sais (lactobionatos), compostos que apresentam aplicações na área farmacêutica, foram obtidos via ação do complexo enzimático glicose-frutose oxidorredutase (GFOR)/gliconolactonase (GL) - presente no periplasma de células da bactéria Zymomonas mobilis - imobilizado em alginato de cálcio. Nas reações catalisadas por este sistema enzimático, o pH do meio deve ser controlado em valores ligeiramente ácidos. Para este fim, foram empregados NaOH, KOH ou Ca(OH)2 e, como consequência, os respectivos sais foram formados. O estudo da cinética de formação dos lactobionatos de sódio, potássio e cálcio e do próprio ácido lactobiônico foi seguido das etapas de purificação, caracterização e avaliação da estabilidade físico-química, visando à potencial utilização destes compostos na área farmacêutica. Em ensaios de bioprodução dos lactobionatos de sódio, potássio e cálcio, foram obtidos rendimentos de 74, 77 e 84%, respectivamente. Em bateladas sucessivas de bioconversão, totalizando 96 h de uso do biocatalisador, rendimentos de 80 e 56 % em lactobionatos de cálcio e de potássio foram atingidos. Na etapa de purificação dos sais, foram alcançados teores de pureza de aproximadamente 95%, sendo então procedida a caracterização dos compostos por cromatografia líquida de alta eficiência, espectrometria de massas e RMN de 13C. Nos estudos de estabilidade acelerada, de longa duração e degradação forçada, os lactobionatos de sódio, potássio e cálcio obtidos nos ensaios de bioconversão conduzidos em maior volume reacional, foram inicialmente purificados e, então, comparados frente ao ácido lactobiônico, obtido por troca iônica a partir do lactobionato de sódio, e com o ácido lactobiônico comercial (Sigma-Aldrich). Nos testes de estabilidade acelerada e de longa duração, foi constatada a estabilidade de todos os compostos por até seis meses quando expostos a 30 e 40oC e 75% de umidade relativa. Por outro lado, a presença da lactobionolactona foi identificada nas amostras dos compostos na forma ácida. Com relação aos testes de degradação forçada, os lactobionatos de sódio, potássio, e cálcio e o ácido lactobiônico se mostraram estáveis frente à exposição a soluções ácidas e alcalinas e às temperaturas avaliadas. Contudo, observou-se degradação no tratamento com solução oxidativa, com cinética de degradação de ordem zero para os sais e de segunda ordem para o ácido lactobiônico. Elevadas concentrações de produtos - lactobionatos de sódio, potássio e cálcio - foram atingidas com a utilização do sistema GFOR/GL imobilizado em alginato de cálcio. Considerando o conjunto de informações obtido, quanto à caracterização físico-química dos compostos produzidos, foi demonstrada a estabilidade frente aos diferentes parâmetros avaliados atendendo aos requisitos mínimos legais para sua aplicação na área farmacêutica.
Keywords: Zymomonas mobilis; Enzimas; Indústria farmacêutica; Biotecnologia; Enzymes; Pharmaceutical industry; Biotechnology